Unsupervised hyperspectral band selection with deep autoencoder unmixing. (3rd July 2022) - Elkholy, Menna M.; Mostafa, Marwa S.; Ebeid, Hala M.; Tolba, Mohamed
ABSTRACT: Hyperspectral imaging (HSI) is a beneficial source of information for numerous civil and military applications, but high dimensionality and strong correlation limits HSI classification performance. Band selection aims at selecting the most informative bands to minimise the computational cost and eliminate redundant information. In this paper, we propose a new unsupervised band selection approach that benefits from the current dominant stream of deep learning frameworks. The proposed approach consists of two consecutive phases: unmixing and cluster. In the unmixing phase, we utilised a nonlinear deep autoencoder to extract accurate material spectra. In the cluster phase, we calculate the variance for each obtained endmember to construct a variances vector. Then, classical K-mean was adopted to cluster the variances vectors. Finally, the optimal band subset was obtained by choosing only one spectral band for each cluster. We carried out several experiments on three hyperspectral datasets to test the feasibility and generality of the proposed approach. Experimental results indicate that the proposed approach surpasses several state-of-the-art counterparts by an average of 4% in terms of overall accuracy.